The Correlation Between Neutrophil-Lymphocyte Ratio (NLR) and Erythrocyte Sedimentation Rate (ESR) in Pneumonia Patients - Ayati, Ismadewi Nur; Ni Luh Gede Puspita Yanti; Didik Prasetya (Jurnal Kesehatan Cendikia Jenius, 2025)
Pneumonia is an acute lung infection that remains a global public health concern due to its high incidence and mortality rates. Early diagnosis is crucial, and laboratory parameters such as the Neutrophil-Lymphocyte Ratio (NLR) and Erythrocyte Sedimentation Rate (ESR) serve as important indicators of inflammation. This study aimed to determine the correlation between NLR values and ESR levels in pneumonia patients at Bhayangkara Hospital Denpasar. This was a correlational analytic study using a retrospective design. A total of 51 hospitalized pneumonia patients were selected through purposive sampling based on medical records from October to December 2024. The data included NLR and ESR values along with patient characteristics, and were analyzed using the Spearman Rank correlation test. The results showed that most patients had high NLR (78.4%) and high ESR (80.4%) values. The statistical analysis revealed a significant and positive correlation between NLR and ESR with a p-value of 0.000 and a correlation coefficient (r) of 0.582, indicating a moderate-strength association. This suggests that an increase in NLR tends to be followed by an increase in ESR. Conclusion: There is a significant correlation between NLR values and ESR levels in pneumonia patients. These findings support the use of both NLR and ESR as complementary inflammatory markers in the clinical monitoring of pneumonia. Further research using primary data and additional parameters is recommended to provide a more comprehensive picture of the inflammatory status in pneumonia cases.